Forms of pupils` free time activities in service of fostering their aesthethic taste - Mitrović, Ljiljana Lj.; Panić, Danijela S.; Lazić, Dragana D. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2018)
This paper deals with the free time activities of pupils, that is, the organized forms of educational work that is realized through the work of sections that are in the service of fostering aesthetic taste. The paper examines the pupils’ opinion on participation in the sections. The sample of this study consists 140 pupils from four elementary schools. The research was carried out using the method of data collection and survey technique and the questionnaire was used as an instrument. The results of the research show that pupils are interested in working in free time activities, that they are not overburdened by the work in them and that they have a positive opinion about cultural and artistic events. Also, the results show the link between pupils’ school achievement and participation in free time activities. The work brings useful knowledge about pupils’ interests.